Implied Meanings Behind Structures Governing Friendly Conversation - Ninuk Krismanti (STKIP PGRI Banjarmasin, 2016)
This paper focuses on the investigation of implied meanings behind structures governing friendly conversation. The friendly conversation becoming the data is the one participated by university colleagues taking place in a dining restaurant. The data are taken in form of spoken discourse which then transcribed into written form of discourse. To reveal the structures of the friendly conversation, the writer applies Francis and Hunston’s model. The structures found then further investigated using the analysis on implicatures. Of the 21 structures found in the data, the implied meanings discussed are divided into four different perspectives: implications behind the highest occurrences of structures, natures of friendly conversation, power, and solidarity. From the research, it can be concluded that the conversation being studied is done in dynamic pace with good engagements among participants. The participants are given equal power to be initiators of the exchanges which show their intimacy to each other. The unequal power distribution is found in the exchanges between participants and the workers of the restaurant where the conversation took place.